2018
DOI: 10.1038/modpathol.2017.171
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance and concordance of HER2 status in local and central testing—an analysis of 1581 HER2-positive breast carcinomas over 12 years

Abstract: Human epidermal growth factor receptor 2 (HER2) is a central predictive biomarker in breast cancer. Inaccurate HER2 results in different laboratories could be as high as 20%. However, this statement is based on data generated more than 13 years ago and may not reflect the standards of modern diagnostic pathology. We compared central and local HER2 testing in a total of 1581 HER2-positive tumors from five clinical trials. We evaluated the clinical relevance for pathological complete response (pCR) and disease-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Several studies reported varying concordance of results between the surgical specimen and core needle biopsy of ER (77.8 to 99%), PR (69 to 97%), and HER2 (64 to 97%), respectively, with particular emphasis placed on a general tendency for higher discrepancies in PR status [22][23][24][25][26][27]. In addition to substantial improvement in receptor measurement accuracy, interlaboratory variation still exists in the assignment of receptor status [28,29]. The choice of method (such as IHC and RT-PCR), the assay method (dual-antibody vs single-antibody ER assay), as well as sample processing (e.g., decalcification reduced staining intensity especially in bone metastasis) may yield to discordant results [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported varying concordance of results between the surgical specimen and core needle biopsy of ER (77.8 to 99%), PR (69 to 97%), and HER2 (64 to 97%), respectively, with particular emphasis placed on a general tendency for higher discrepancies in PR status [22][23][24][25][26][27]. In addition to substantial improvement in receptor measurement accuracy, interlaboratory variation still exists in the assignment of receptor status [28,29]. The choice of method (such as IHC and RT-PCR), the assay method (dual-antibody vs single-antibody ER assay), as well as sample processing (e.g., decalcification reduced staining intensity especially in bone metastasis) may yield to discordant results [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…In locoregional breast cancer, discordant HER2 results were reported to be associated with lower pathological complete remission rates after neoadjuvant systemic therapy. However, the discordance rate between local and central HER2 testing has dramatically improved from 52% to 8% over a period of 12 years in breast cancer [29]. In the GASTRIC-5 registry we did not see a statistically significant learning effect of HER2 testing over time (Figure 2).…”
Section: Discussionmentioning
confidence: 86%
“…There are recent evidences that support the role of immune-related factors in BC prognosis and treatment, and in particular, TILs represent a crucial factor in this scenario. Most of TNBCs and HER2-positive BCs have dense immune infiltrates, and some studies showed that the presence of TILs in tumor tissue may predict response to neoadjuvant therapy [10] and also may have a significant prognostic value after adjuvant chemotherapy [[11], [12], [13], [14]]. Although the concept of evaluating TILs in BC and making correlations with clinical outcome is not new, yet there are few consistent data to consider TILs as reliable prognostic factors because of same complex and controversial aspects [15].…”
Section: Discussionmentioning
confidence: 99%